Validation of the World Health Organization Disability Assessment Schedule II (WHODAS-II) in patients with multiple sclerosis. (April 2015) - Magistrale, Giuseppe; Pisani, Valerio; Argento, Ornella; Incerti, Chiara C; Bozzali, Marco; Cadavid, Diego; Caltagirone, Carlo; Medori, Rossella; DeLuca, John; Nocentini, Ugo
Background: The World Health Organization Disability Assessment Schedule (WHODAS-II) is a widely used generic assessment instrument for health and disability. However, a specific psychometric evaluation for this scale in multiple sclerosis (MS) is lacking. This study is aimed at the assessment of the psychometric properties of the WHODAS-II in MS with Cronbach's α and modern Rasch-model analyses. Methods: The WHODAS-II was administered to 136 consecutively recruited MS patients. Several indexes of fit to the Rasch model were evaluated in order to assess internal construct validity. Internal consistency was assessed with Cronbach's α and the Person Separation Index (PSI). External validity was evaluated by analyzing correlations between the WHODAS-II and the Multiple Sclerosis Quality of Life-54 (MSQoL-54). Results: Classical reliability indexes (Cronbach's α and intraclass correlation) showed good to excellent reliability for most of the subscales and for the total scale (α = 0.93). The total scale both with (36 items) or without (32 items) work items reached good fit to the Rasch model (PSI = 0.83). However, analysis of the subscales could resolve only four subscales out of seven. Conclusions: The WHODAS-II is a reliable and valid instrument for the assessment of patient-reported disability in MS, with some limitations including some item redundancy and questionable reliability of some subscales.